Effectivity and safety of trifocal intraocular lenses and capsular tension rings implantation for cataract patients with axial high myopia - Shan Hua; Qiu-Xia Xie; Hu Wang; Jing-Xiang Zhong (International Journal of Ophthalmology, 2024)
AIM: To assess effectivity and safety of trifocal intraocular lenses (IOLs) and capsular tension rings in treating cataract patients with axial high myopia. METHODS: A prospective nonrandomized controlled clinical trial was conducted. Totally 98 eyes (74 patients) who underwent femtosecond laser-assisted cataract surgery (FLACS) with trifocal IOLs were enrolled in the study and followed up for 2y after surgery: 46 eyes (33 patients) with capsular tension ring implantation in the long axial lengths (AL) group (26<AL<29 mm) and 52 eyes (41 patients) in the normal AL group (22<AL<24.5 mm). Postoperative outcomes about effectivity and safety, including the subjective and objective visual quality, and postoperative complications were assessed. RESULTS: Uncorrected distance visual acuity at 5 m and uncorrected intermediate visual acuity at 60 and 80 cm in the long AL group were significantly worse than those in the normal AL group at 3mo postoperatively (P<0.05). The differences in reading speed, spectacle independence and potential visual complaints between the two groups were not statistically significant (P>0.05). The dysfunctional lens index and total modulation transfer function (MTF) average height were similar between the two groups. The postoperative internal coma aberrations in the axial high myopia eyes were significantly higher than that in the normal AL group (P<0.05). The total satisfaction score in the long AL group (91.32±2.76) was slightly higher than that in the normal AL group (90.36±3.47), but there was no difference (P=0.136). A statistically negative correlation was found between corrected distance visual acuity (CDVA) and dysfunctional lens index (r=-0.382, P=0.009), and between CDVA and the total MTF average height (r=-0.374, P=0.01). But there was no significant correlation between CDVA and total satisfaction score (r=0.059, P=0.696). Postoperative complications mainly presented as posterior capsular opacity (PCO), retinal detachment and cystoid macular edema. There was no difference in the incidence of fundus disease (6.5% vs 3.8%, P=0.663) or PCO (17.4% vs 7.7%, P=0.217) between the two groups at two years. CONCLUSION: The utilization of trifocal IOL and capsular tension ring implantation is beneficial for cataract patients with axial high myopia undergoing FLACS. This approach not only ensures excellent subjective feelings and objective visual quality, but also does not increase the incidence of postoperative complications.